Kartagener Syndrome: A Rare Cause of Infertility - Kadir Bakay; Davut Güven; İdris Koçak (Gynecology Obstetrics & Reproductive Medicine)
Kartagener’s syndrome is defined as motility dysfunction of the epithelial cilia lining the respiratory tract, fallopian tubes and the flagella of the sperm and genetically classified as a rare autosomal recessive disease consisting almost half of all primary ciliary dyskinesia cases. In this brief case review we aim to share our experience concerning Kartagener’s syndrome from a gynecologic point of view regarding an unexplained infertility patient.